Real-time magnetic resonance imaging–guided radiofrequency atrial ablation and visualization of lesion formation at 3 Tesla - Vergara, Gaston R.; Vijayakumar, Sathya; Kholmovski, Eugene G.; Blauer, Joshua J.E.; Guttman, Mike A.; Gloschat, Christopher; Payne, Gene; Vij, Kamal; Akoum, Nazem W.; Daccarett, Marcos; McGann, Christopher J.; MacLeod, Rob S.; et al. (Heart rhythm, 2011)
Magnetic resonance imaging (MRI) allows visualization of location and extent of radiofrequency (RF) ablation lesion, myocardial scar formation, and real-time (RT) assessment of lesion formation. In this study, we report a novel 3-Tesla RT -RI based porcine RF ablation model and visualization of lesion formation in the atrium during RF energy delivery. The purpose of this study was to develop a 3-Tesla RT MRI-based catheter ablation and lesion visualization system. RF energy was delivered to six pigs under RT MRI guidance. A novel MRI-compatible mapping and ablation catheter was used. Under RT MRI, this catheter was safely guided and positioned within either the left or right atrium. Unipolar and bipolar electrograms were recorded. The catheter tip–tissue interface was visualized with a T1-weighted gradient echo sequence. RF energy was then delivered in a power-controlled fashion. Myocardial changes and lesion formation were visualized with a T2-weighted (T2W) half Fourier acquisition with single-shot turbo spin echo (HASTE) sequence during ablation. RT visualization of lesion formation was achieved in 30% of the ablations performed. In the other cases, either the lesion was formed outside the imaged region (25%) or the lesion was not created (45%) presumably due to poor tissue–catheter tip contact. The presence of lesions was confirmed by late gadolinium enhancement MRI and macroscopic tissue examination. MRI-compatible catheters can be navigated and RF energy safely delivered under 3-Tesla RT MRI guidance. Recording electrograms during RT imaging also is feasible. RT visualization of lesion as it forms during RF energy delivery is possible and was demonstrated using T2W HASTE imaging.